Human Values and Human rights - "Dharmadhikari, D. M." (New Delhi, 2017)
The Human Rights Jurisprudence in India is developing in leaps and bounds by the Apex Court of this country which, case-by-case is taking help of International Human Rights Declarations, Covenants and Instruments in understanding and amplifying the declared Fundamental Rights in the Constitution of India. In the present book various dimensions of human rights like right to health, education, rights of elder citizens, mentally ill, women, etc. have been covered. There are also articles on the need to inculcate human values to make people in and outside Government conscious of their fundamental human duties which are necessary for developing mutual respect for human rights of various categories of persons and citizens of the country. The book examines the field of Human Rights and indicates various fields where the need of Human Rights' approach in and outside government is becoming more and more crucial.
Keywords: Law